The Lexical Representation of Happiness (Joy) in the Slovene Language (Based on Material From Pleteršnik’s Dictionary and the SSKJ) - Voršič, Ines (ZORA 160: Imenitnost slovenščine sto let po Pleteršniku, 2026)
Happiness (i.e. joy) is an intense and pleasant emotion that positively influences relationships with others. At the same time, language plays an important role in connecting people;. This paper, therefore, examines how joy is reflected in the Slovene language. With focus being on word-formation, the study zeros in on word-formational morphemization and the gradability of derived forms motivated by the non-derived base adjective vesel (“joyful”) in Pleteršnik’s Dictionary and the SSKJ.